NOMADS, WANDERES AND QUEERING: ON THE QUEERNES OF BECOMING QUEER - Freitas, Cledione J. [UNESP]; Justo, Jose S. [UNESP]; Peres, Wiliam S. [UNESP] (Univ Federal Paraiba, 2017)
Homeless people, wanderers and roamers constitute a mode of nomadism whose main characteristic is walking through the streets of cities and roadsides of highways. Such way of life differs from the conventional ones because it gives up fixed housing and residence in order to produce life in open spaces, from work to love. The purpose of this article is to discuss the use of urban spaces for homeless people, wanderers and roamers through field observations, using as reference the queer theory. It was found that the use of urban spaces made by these erring nomads was at odds with the conventional and standardized uses, arousing feelings of strangeness and eccentricity and, therefore, they can be understood as queering practices.
Keywords: Nomads; Wandering; Queer Theory